Characterizing the Contaminant-Adhesion of a Dibenzofuran Degrader Rhodococcus sp. - Yu Chen; Qingquan Wei; Xudi Wang; Yanan Wu; Changai Fu; Xu Wang; Hangzhou Xu; Li Li (Microorganisms)
The adhesion between dibenzofuran (DF) and degrading bacteria is the first step of DF biodegradation and affects the efficient degradation of DF. However, their efficient adhesion mechanism at the molecular level remains unclear. Therefore, this study first examined the adhesive behaviors and molecular mechanisms of Rhodococcus sp. strain p52 upon exposure to DF. The results showed that the adhesion between strain p52 and DF is mediated by extracellular polymeric substances (EPSs). Compared with sodium acetate as a carbon source, the percentages of glucose and proteins related to electron transfer, toxin–antitoxin, and stress responses were elevated, which were analyzed by polysaccharide composition and proteomics, and the contents of extracellular polysaccharides and proteins were increased. Moreover, biofilm analysis suggested an increase in EPS content, and the change in components increased biofilm yield and promoted loose and porous aggregation between the bacteria; this aggregation caused an increase in the specific surface area in contact with DF. The surface characteristics analysis indicated that the production of EPS reduced the absolute value of the zeta potential and increased the hydrophobicity of strain p52, which was beneficial for the adhesion of strain p52 and DF. These findings help us to enhance the understanding of the adhesion mechanisms and bioremediation of polycyclic aromatic hydrocarbons by degrading bacteria.